1987
DOI: 10.1002/aic.690330205
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐side ion exchange mass transfer in a ternary system

Abstract: Liquid phase mass transfer in a ternary system [ R -A ] + ( B + €) has been analyzed according to the Nernst-Planck equation. The equilibrium isotherm was represented by the mass action law. In the case of D,, > DB > DE, the resin phase concentration of B ion with time showed a peak. The height of the peak was influenced by the diffusivity ratio, equilibrium constant, and ionic valence. When the modified equilibrium constant K' 2 100 in the case of A ion and K' 2 500 in the case of Band €ions, the exchange rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…First, let us consider the membrane-phase mass transport. If no co-ion, an anion, exists in the membrane and counterions transport in one direction, and mass flux of each ion in the membrane can be represented on the basis of the Nernst-Planck equation (Kataoka et al, 1987) as follows:…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…First, let us consider the membrane-phase mass transport. If no co-ion, an anion, exists in the membrane and counterions transport in one direction, and mass flux of each ion in the membrane can be represented on the basis of the Nernst-Planck equation (Kataoka et al, 1987) as follows:…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…However, one common characteristic of all three models is that they produce a linear function that relates effluent concentration to running time. Further work by Kataoka [31,32] showed the influence of diffusion coefficient on computation. Lin, X. et al [33], Aurélie et al [34], Yang, J. et al [35], and Murillo, R. et al [36] also produced methods for modeling ion exchange.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is one of the most important assumptions of MBIE modeling. Kataoka et al (1987) . They showed that the electric field, caused by the difference of their respective diffusivities, has a significant effect on the ion exchange rate of a binary system.…”
Section: Mbie-sim Backgroundmentioning
confidence: 99%
“…They showed that the electric field, caused by the difference of their respective diffusivities, has a significant effect on the ion exchange rate of a binary system. 16 Haub and Foutch (1984) studied the film-diffusion controlled liquid-side mass transfer in a ternary system. Flux expressions for the ions with equal valences and ions with different valences were developed separately.…”
Section: Mbie-sim Backgroundmentioning
confidence: 99%